The Army times book of great land battles from the Civil War to the Gulf War - Morelock, J.D. 1946- (Berkley Books, 1994)
From the Civil War's Battle of Gettysburg to the Gulf War's brilliantly orchestrated, 100-hour AirLand Battle, award-winning Army historian Colonel J.D. Morelock brings a lifetime of research and military experience to fourteen in-depth accounts of the world's most important battles. With rare insight and "you are there" immediacy, he captures the drama and excitement of each confrontation--from the vast historical perspective of global events, to the ever-changing developments in strategy, weaponry and technology, to the personal contributions of commanders and soldiers whose individual stories of courage reveal the human side of war. An invaluable addition to every military library.